Suspendendo a (Des)Crença? Diversidade cultural e religião na Europa contemporânea - Jorge Botelho Moniz (Araucaria)
This paper analyzes the conditions of (dis)belief in contemporary Europe within a context of strong and growing cultural diversity. We examine the (theoretical and empirical) state of the art regarding the results of previous studies on the binomial religion-diversity. We observe that diversity is usually negatively associated with religious cohesion and vitality. The fragmenting and relativizing effects of diversity and the growth of an implicit or explicit secular culture are usually referred to as the primary sources for the weakening of religious ties, especially traditional/institutional ones. However, most researchers have resisted affirming this negative correlation, speaking only of displacement and recomposition of religion in diversity conditions. We conclude that this assertion has validity; nevertheless, it becomes hard to deny that diversity has secularizing, although limited, effects on religion, chiefly because of the emergence and hegemony of an immanent paradigm of interpreting the world.